Like father like daughter: sex-specific parent-of-origin effects in the transmission of liability for psychotic symptoms to offspring. (29th August 2018) - Aylott, A.; Zwicker, A.; MacKenzie, L. E.; Cumby, J.; Propper, L.; Abidi, S.; Bagnell, A.; Fisher, H. L.; Pavlova, B.; Alda, M.; Uher, R.
Abstract: Children of parents with major mood and psychotic disorders are at increased risk of psychopathology, including psychotic symptoms. It has been suggested that the risk of psychosis may be more often transmitted from parent to opposite-sex offspring (e.g., from father to daughter) than to same-sex offspring (e.g., from father to son). To test whether sex-specific transmission extends to early manifestations of psychosis, we examined sex-specific contributions to psychotic symptoms among offspring of mothers and fathers with depression, bipolar disorder and schizophrenia. We assessed psychotic symptoms in 309 offspring (160 daughters and 149 sons) aged 8–24 years (mean=13.1, s.d. =4.3), of whom 113 had a mother with schizophrenia, bipolar disorder or major depression and 43 had a father with schizophrenia, bipolar disorder or major depression. In semi-structured interviews, 130 (42%) offspring had definite psychotic symptoms established and confirmed by psychiatrists on one or more assessments. We tested the effects of mental illness in parents on same-sex and opposite-sex offspring psychotic symptoms in mixed-effect logistic regression models. Psychotic symptoms were more prevalent among daughters of affected fathers and sons of affected mothers than among offspring of the same sex as their affected parent. Mental illness in the opposite-sex parent increased the odds of psychotic symptoms (odds ratio (OR)=2.65, 95% confidence interval (CI) 1.43–4.91, P =0.002), but mental illness in the same-sex parent did not have a significant effect on psychotic symptoms in offspring (OR=1.13, 95% CI 0.61–2.07, P =0.697). The opposite-sex-specific parent-of-origin effects may suggest X chromosome-linked genetic transmission or inherited chromosomal modifications in the etiology of psychotic symptoms.